MEC App: Enhancing Legal Knowledge via Smartphone. - Abd Ghadas, Z. A.; Haron, A. S. (Pertanika Journal of Social Sciences & Humanities)
Knowledge and advancement in technology are indispensable in today's living. One of the most popular products is the smartphone. As smartphones continue to grow in popularity, it is important to look into how legal education and understanding could be enhanced via applications (apps) available in the smartphone. This paper discusses how smartphone application could enhance understanding of the Malaysia Federal Constitution among the public, academics and legal practitioners. The app, named MEC contains all provisions of the Constitution is invented to replace the print version whose bulk has long been a problem for students to bring it to the class. The app was developed using Rapid Application Development (RAD) methodology, a common method used in computer software and mobile apps development.